Collaboration and Supply Chain Integration Strategies in The Textile Industry to Anticipate the Increase in Demand Post Covid-19 - Respati, Putra Panji; Kurniawan, Aries; Cahyadi, Nur; Setiawan, Heri Cahyo Bagus (UMSurabaya Publishing, 2024)
This research aims to find out what business innovation strategies are being implemented by several textile entrepreneurs to achieve momentum for improving this industry while business risks can be minimized. This phenomenological research was carried out using interviews, observations and document studies at several textile companies in Central Java. The novelty in this research answers the phenomenon that occurred in the textile industry after the COVID-18 pandemic outbreak. The research results show that two strategies are most dominantly used: First, the collaboration strategy, companies collaborate with other companies to share risks and profits. Second, a supply chain integration strategy by controlling companies located upstream and downstream in the textile industry to secure production and control the market